Control of Prosthetic Hands via the Peripheral Nervous System - Ciancio, Anna Lisa; Cordella, Francesca; Barone, Roberto; Romeo, Rocco Antonio; Bellingegni, Alberto Dellacasa; Sacchetti, Rinaldo; Davalli, Angelo; Di Pino, Giovanni; Ranieri, Federico; Di Lazzaro, Vincenzo; Guglielmelli, Eugenio; Zollo, Loredana (Frontiers in Neuroscience, 2016)
This paper intends to provide a critical review of the literature on the technological issues on control and sensorization of hand prostheses interfacing with the Peripheral Nervous System (i.e. PNS), and their experimental validation on amputees. The study opens with an in-depth analysis of control solutions and sensorization features of research and commercially available prosthetic hands. Pros and cons of adopted technologies, signal processing techniques and motion control solutions are investigated. Special emphasis is then dedicated to the recent studies on the restoration of tactile perception in amputees through neural interfaces. The paper finally proposes a number of suggestions for designing the prosthetic system able to re-establish a bidirectional communication with the PNS and foster the prosthesis natural control.